2005
DOI: 10.1103/physrevd.72.107701
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of supersymmetric gauge theory in the uneliminated component formalism

Abstract: We show that the renormalisation of the N = 1 supersymmetric gauge theory when working in the component formalism, without eliminating auxiliary fields and using a standard covariant gauge, requires a non-linear renormalisation of the auxiliary fields.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…Although they found divergent contributions which broke supergauge invariance, their final result was gauge-invariant without the need for any redefinition. In subsequent work [14] it was shown that the N = 1 2 superfield action requires modification to ensure renormalisability, which is consistent with our findings in the component formulation [12].…”
supporting
confidence: 88%
See 3 more Smart Citations
“…Although they found divergent contributions which broke supergauge invariance, their final result was gauge-invariant without the need for any redefinition. In subsequent work [14] it was shown that the N = 1 2 superfield action requires modification to ensure renormalisability, which is consistent with our findings in the component formulation [12].…”
supporting
confidence: 88%
“…As we noted in Refs. [11], [12], at the quantum level the U (N ) gauge invariance cannot be retained.…”
Section: The Classical Adjoint Action Without Superpotentialmentioning
confidence: 99%
See 2 more Smart Citations
“…Afterwards, the perturbative methodology was successfully applied for different N = 2 Wess-Zumino model whose renormalization properties have been discussed in [7][8][9], N = 1 2 supersymmetric gauge theories whose formulation and renormalizability have been studied in [10,11] (see also [12][13][14][15] for discussions on this issue), and extended supersymmetric theories, in particular, those ones formulated in terms of the harmonic superspace [16,17]. The calculation of the superfield effective potential for this kind of theories [18][19][20][21] also deserves to be mentioned.…”
mentioning
confidence: 99%